FACTORS AFFECTING THE FISCAL DECENTRALIZATION OF LOCAL GOVERNMENTS - Ghina Kamila Sofa (Jurnal Proaksi, 2021)
This study aims to examine and find out about the factors that influence the case study Fiscal Decentralization in the City of Tasikmalaya. Data collection is done by collecting secondary data in the form of LRA Kota Tasikmalaya in 2008-2020. The method of analysis used in this research is the descriptive method. Multiple linear regression analysis was used for data analysis. The influence of Local Own Revenue (PAD) and Balanced Funds on Fiscal Decentralization is concluded from the results of research that has been conducted by the author showing the influence of Local Own Revenue (PAD) and Balancing Funds on Fiscal Decentralization. PAD has a positive effect on Fiscal Decentralization, and for Balanced Funds has a negative effect on Fiscal Decentralization